The effect of rehabilitating exercises by using a therapeutic medium on some motor abilities of hemiplegia patients - Abdul-Sttar Khalil, Lamyaa; Kadhim Abdalkarim, Entsar (International Journal of Psychosocial Rehabilitation, 2020)
Cerebral palsy "is one of the diseases that afflict children, and it is a term given to the condition of a child who is exposed to a normal brain injury by accident due to its inability to grow or damage to the cells of the areas responsible for movement and knowledge of strength and balance during the stage of normal development." (116: 1999: 10) Cerebral palsy causes disruption in movement and posture due to damage to brain cells in areas that control and coordinate muscle tone, reflexes, strength, and movement. The degree and location of brain damage vary greatly between people with paralysis, as well as the severity of disability and symptoms, as they fall into severe to very simple, and cerebral palsy is one of the diseases that cause a child to be unable to move normally due to damage to brain cells, and this affects his growth despite this. These children have legitimate rights to live independently if services, means, and rehabilitation programs are available to them that develop their mobility abilities and prepare the necessary capabilities for their growth and take care of them during their various stages of development. The simple cerebral does not rise to what exists in other developed countries, and that the exercises given to the injured need to be reorganized in terms of time and effort, and this situation indicates a problem that must be developed solutions from here came the importance of preparing rehabilitative exercises using a therapeutic medium to improve some movement abilities of children with hemiplegia Helping them to move and control their body parts in a balanced and healthy way.